2020
DOI: 10.1093/cvr/cvaa219
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 is a key regulator of endothelial microRNA expression under proatherogenic stimuli

Abstract: Aims Oxidized phospholipids and microRNAs (miRNAs) are increasingly recognized to play a role in endothelial dysfunction driving atherosclerosis. NRF2 transcription factor is one of the key mediators of the effects of oxidized phospholipids, but the gene regulatory mechanisms underlying the process remain obscure. Here, we investigated the genome-wide effects of oxidized phospholipids on transcriptional gene regulation in human umbilical vein endothelial cells (HUVECs) and aortic endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 69 publications
(78 reference statements)
3
17
0
Order By: Relevance
“…MiR-100-5p is believed to have anti-atherosclerotic effects because it inhibits the proliferation of endothelial cells and migration of blood vessels and smooth muscle cells ( Shoeibi, 2020 ). In a mouse model of atherosclerosis, the expression of miR-100-5p can improve endothelial function, weaken atherosclerosis, and reduce plaque area ( Linna-Kuosmanen et al, 2020 ). Further studies indicate that downregulation of miR-100-5p activates the VEGFA/MYC pathway, which leads to increased endothelial cell metabolism, proliferation, and angiogenesis, thereby promoting angiogenesis ( Pankratz et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-100-5p is believed to have anti-atherosclerotic effects because it inhibits the proliferation of endothelial cells and migration of blood vessels and smooth muscle cells ( Shoeibi, 2020 ). In a mouse model of atherosclerosis, the expression of miR-100-5p can improve endothelial function, weaken atherosclerosis, and reduce plaque area ( Linna-Kuosmanen et al, 2020 ). Further studies indicate that downregulation of miR-100-5p activates the VEGFA/MYC pathway, which leads to increased endothelial cell metabolism, proliferation, and angiogenesis, thereby promoting angiogenesis ( Pankratz et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have identified that miRNAs are attracting more attention due to their key regulatory roles in the pathogenesis of AS [ 10 , 11 ]. For example, literature has reported that miR-590 could inhibit atherosclerotic lesion in the in vivo models of AS and facilitate the proliferation and suppress the apoptosis of ox-LDL-treated human aortic endothelial cells [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can regulate gene expression at the posttranscription level and play an important role in human growth, development, physiology, and pathology [ 9 ]. Numerous researches have reported that miRNAs are involved in almost all steps of AS, including the injury and dysfunction of endothelial cells and vascular smooth muscle cells [ 10 , 11 ]. Liu et al [ 12 ] proved that miR-130a was up-regulated in AS mice, and miR-130a knockdown suppressed the inflammation of LPS-induced human umbilical vein endothelial cells (HUVECs) in an in vitro model of AS.…”
Section: Introductionmentioning
confidence: 99%
“…80 We can hypothesise that miR-425-3p and miR-4277 may form a negative feedback loop on the increasing level of this nutrient in VT/VN. Interestingly, miR-425-3p was included in the list of miRNAs regulated by the activity of nuclear factor erythroid 2-related factor 2 (Nrf2), 81 a transcription factor involved in the regulation of metabolism downstream of nutrient-sensing pathways, whose activity is pivotal for the gastrointestinal tract development and maintenance. 82 MiRNAs are present in all eukaryotes: an intriguing aspect is that they could potentially 'traverse' from plants to animals through food via the gastrointestinal tract and access host cellular targets, where they could work as bioactive compounds and influence recipients' physio-pathological conditions.…”
Section: Discussionmentioning
confidence: 99%